Chicana without apology = Chicana sin vergüenza : the new Chicana cultural studies - Torres, Edén E. (Routledge, 2003)
By approaching Chicana/o issues from the frames of feminism, social activism, and cultural studies, and by considering both lived experience and the latest research, Torres offers a more comprehensive understanding of current Chicana life. Through compelling prose, Torres masterfully weaves her own story as a first-generation Mexican American with interviews with activists and other Mexican-American women to document the present fight for social justice and the struggles of living between two worlds.